Synthesis of 3-(2’ ,6’ Dimethyl 5’ -Heptenyl) Bicyclo (2, 2, 1) 5-heptene 2-Carboxylic Acid and its Ethyl Ester by Diels Alder Reaction and Preparation of 3-Methyl-3-(4-methyl 3’ -Pentenyl) Bicyclo (2, 2, 1) 5 Heptene 2-Carboxylic A - Limaye, P.A.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
In this work, attempts have been made to prepare bicyclic compounds using citral or citronellal derivatives by Diels Alder reactions.